Using Ergometer and Timing Activities in Determining the Manpower Required in Chosen Units of Laboratory in the Shiraz Faghihi Hospital - Tahereh Shafaghat; Emmanuel Ugwa; Kofi Aduo-Adjei; Mohammad-Kazem (Baqiyatallah University of Medical Sciences, 2016)
Background: The quantity and quality of manpower, especially in health systems, are major factors affecting speed of service delivery, cost, and accuracy, or, in other words, the quality of service. Objective: This study purposed to investigate the manpower required in various units of the laboratory at Shiraz Faghihi Hospital. Methods: This is a cross-sectional and descriptive-analytical research conducted on all testing processes in the fields of parasitology, hormone biology, microbiology, and urinalysis performed at the studied hospital. The Westinghouse ergometer and timing method was used to estimate manpower requirements, and SPSS18 software was used to analyze data. Results: The average standard time of every duty cycle in parasitology units, hormone biology, microbiology, and urinalysis are 12, 5, 9, and 5 minutes, respectively. The numbers of human resources required in said units were estimated to be 2.6, 3, 4, and 3.7 respectively. In parasitology unit there is lack of 1 manpower. In hormone unit there are two manpower surpluses. In biology unit there is one manpower surplus and urinalysis unit is estimated to be proportional to the number of troops. Conclusion: It is suggested that new, scientific tools be used to evaluate the status of department staff and make improvements to avoid the high costs and difficulties that manpower shortages and surpluses cause for the organization.